2015
DOI: 10.1039/c4tb01664e
|View full text |Cite
|
Sign up to set email alerts
|

Water-based synthesis of cationic hydrogel particles: effect of the reaction parameters and in vitro cytotoxicity study

Abstract: Micro/nanoscale hydrogel particles are of great interest for biomedical applications, such as carriers for therapeutic delivery. Compared to conventional hydrogel particles that are mainly composed of vinylic monomers, we have introduced a simple methodology to prepare multi-functional cationic hydrogel particles by adopting the epoxy-amine chemistry in water exemplifying "click" characteristics. Herein, we investigate the effects of key reaction parameters, including time, temperature, reactant concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…In general, positively charged hydrogels are less frequently utilized and are typically adopted for situations where their charge is key for the application (a feature that would be negated by our complexation-based technique). Moreover, cationic hydrogels in general are more cytotoxic 16 and therefore less commonly used for applications intended to grow cells in before charge neutralization. Therefore, we intended to focus more on the shrinking abilities of negatively charged hydrogels (i.e., HAMA, GelMA, and alginate), with a brief demonstration also on the shrinking of positively charged hydrogels (chitosan).…”
Section: Resultsmentioning
confidence: 99%
“…In general, positively charged hydrogels are less frequently utilized and are typically adopted for situations where their charge is key for the application (a feature that would be negated by our complexation-based technique). Moreover, cationic hydrogels in general are more cytotoxic 16 and therefore less commonly used for applications intended to grow cells in before charge neutralization. Therefore, we intended to focus more on the shrinking abilities of negatively charged hydrogels (i.e., HAMA, GelMA, and alginate), with a brief demonstration also on the shrinking of positively charged hydrogels (chitosan).…”
Section: Resultsmentioning
confidence: 99%
“…Among the various types of HPs that have been reported to date, we selected the one prepared from monomers of bisepoxide and aliphatic polyetheramine largely because of the cationic characteristic of the resulting particles and the ease of preparation. , For neuronal cultures, it is widely shown that surface treatments of culture substrates with cationic polymers such as polylysine, polyornithine, or PEI can greatly improve neuron adhesion to the substrates. , Thus, HPs carrying positive charges can provide a chemical-cue based strategy to modulate neuron adhesion. As shown in Figure , the prepared HPs used in this study have an average surface charge of +60 mV with intensity average hydrodynamic diameter being 410 nm based on DLS measurements.…”
Section: Resultsmentioning
confidence: 99%
“…The details of the hydrogel particle (HP) preparation have been described elsewhere. , Briefly, Jeffamine T-403 polyetheramine (Huntsman) and 1,3-butadiene diepoxide (Aldrich) were mixed at the molar ratio of 2:3 (Jeffamine/diepoxide) to a final monomer concentration of 15 wt % in water. The resulting solution was first incubated at 65 °C for 10 min before it was diluted to 0.5 wt % and further reacted for 30 min.…”
Section: Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Acrolein released in large quantities from disordered cells mediates a sequential [4+4] imino‐polymerization reaction with polyamines to yield a diazacyclooctane hydrogel. This highly cationic and conformationally flexible hydrogel can induce cell death when it adheres firmly to negatively charged cell surfaces [16a,20] …”
Section: Exploring the Reactivity Of Acrolein Imines And Functional Smentioning
confidence: 99%